2017
DOI: 10.1007/s12640-017-9830-x
|View full text |Cite
|
Sign up to set email alerts
|

Methionine Administration in Pregnant Rats Causes Memory Deficit in the Offspring and Alters Ultrastructure in Brain Tissue

Abstract: In the present work, we evaluated the effect of gestational hypermethioninemia on locomotor activity, anxiety, memory, and exploratory behavior of rat offspring through the following behavior tests: open field, object recognition, and inhibitory avoidance. Histological analysis was also done in the brain tissue of pups. Wistar female rats received methionine (2.68 μmol/g body weight) by subcutaneous injections during pregnancy. Control rats received saline. Histological analyses were made in brain tissue from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 24 publications
3
11
1
1
Order By: Relevance
“…If there are morphological changes as adaptation or response to a certain stress, mitochondria can signal survival or cell death depending on the severity of insult (Kasahara and Scorrano, 2014). These data indicate the extent of insult caused by excessive Met in maternal environment and agreed with our recent study (Schweinberger et al, 2017b).…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…If there are morphological changes as adaptation or response to a certain stress, mitochondria can signal survival or cell death depending on the severity of insult (Kasahara and Scorrano, 2014). These data indicate the extent of insult caused by excessive Met in maternal environment and agreed with our recent study (Schweinberger et al, 2017b).…”
Section: Discussionsupporting
confidence: 94%
“…Since the adequate functioning of Na + , K + ‐ATPase is essential for nerve impulse conduction, the reduction of its activity may also lead to decreased memory and learning capacity (Wyse et al, 2004; Dos Reis‐Lunardelli et al, 2007; Vanzella et al, 2017) and that melatonin partially prevented Na + , K + ‐ATPase activity at 30‐day old pups, in the present study we also evaluated whether melatonin could prevent memory alterations observed in the offspring at 30‐day old born hypermethioninemic rats (Schweinberger et al, 2017b). In the present study we showed that male 30‐day‐old pups exposed to Met during gestation bear learning and memory impairments (water maze tasks).…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations